"A Merry Christmas" - Truman State University, Pickler Memorial Library Special Collections, University Archives (Owner, Digitizing Technician) (1910)
Christmas postcard with a vase of holly leaves and berries; to Mrs. Fannie Anderson; postmarked December 24, 1910.